Evaluation of the physical properties of andaliman (Zanthoxylum acanthopodium DC) fruit extract tablets using polyvinylpyrrolidone as a binder agent - Turnip, Monika Maristella; Sunarti, Sunarti; Nawangsari, Desy (Acta Pharmaciae Indonesia, 2023)
Background: Zanthoxylum acanthopodium DC, also known as andaliman, is a traditional herb utilized predominantly as a spice. It is rich in bioactive compounds such as alkaloids, flavonoids, tannins, saponins, and terpenoids, which exhibit analgesic activities. Objective: This study aims to develop a tablet formulation of andaliman fruit extract, employing polyvinyl pyrrolidone (PVP) K-30 as a binder, utilizing the wet granulation method. Method: The andaliman fruit was processed to extract its components using 96% ethanol. The extract, at a concentration of 100 mg, was then formulated into three different tablet formulations, varying in PVP K-30 concentration: F1 (1%), F2 (3%), and F3 (5%). These formulations were analyzed for granule characteristics and physical properties of the tablets. Results: Granule testing confirmed that all formulations met the requirements for quality granules. Among the formulations, F1 (1% PVP concentration) demonstrated superior physical properties: size uniformity of 1.22±0.00 cm, weight uniformity of 518.53±10.15 mg, friability of 0.45±0.01%, hardness of 6.34±0.05 kg, and disintegration time of 9.42±0.90 minutes. Conclusion: The tablet formulation of Andaliman fruit extract with 1% PVP K-30 exhibited the most favorable physical properties, suggesting its potential viability for further development and testing. This study lays the groundwork for exploring Andaliman fruit-based analgesic tablets.